Utility of faecal calprotectin in inflammatory bowel disease (IBD): what cut-offs should we apply?. Issue 1 (17th March 2014) - Dhaliwal, A; Zeino, Z; Tomkins, C; Cheung, M; Nwokolo, C; Smith, S; Harmston, C; Arasaradnam, R P
Abstract : Background: Faecal calprotectin (FC), a cytosolic protein released by neutrophils (S100 family) in response to inflammation, is a simple, non-invasive test that can be used to differentiate irritable bowel syndrome (IBS) with inflammatory bowel disease (IBD), where there can be considerable symptom overlap. Aims and methods: The aims of the study were (1) to be able to predict the ability of FC to exclude IBD and determine cut-offs when in remission, (2) to investigate the effects of time and temperature on stability of FC and (3) compare three ELISA kits to measure FC: Buhlmann, PhiCal v1 and PhiCal v2. A total of 311 patients with altered bowel habit were tested for FC; 144 with IBS, 148 with IBD and 19 with other organic causes. Results: Sensitivity and specificity of FC (with PhiCal v2 kit) to distinguish between functional disorder (IBS) and IBD using cut-off 50 μg/g were 88% and 78%, respectively, with a negative predictive value of 87%. Area under the receiver operating curve was 0.84 (CI 0.78 to 0.90). For those with IBD, FC values below 250 μg/g corresponded with remission of disease with a sensitivity and specificity of 90% and 76%, respectively. Area under the receiver operating curve was 0.93 (CI 0.89 to 0.97). FC was stable once extracted and frozen for up to 2.5 months. Pearson correlation was good between Buhlmann assay and PhiCal v2 (r 2  = 0.95). Conclusions: FC has up to 87% negative predictive value to exclude IBD, and cut-offs less than 250 μg/g had 90% sensitivity to determine remission in IBD. Once frozen, FC is stable and the ELISA monoclonal plates were broadly comparable.